2015
DOI: 10.1371/journal.ppat.1005127
|View full text |Cite
|
Sign up to set email alerts
|

Leptomonas seymouri: Adaptations to the Dixenous Life Cycle Analyzed by Genome Sequencing, Transcriptome Profiling and Co-infection with Leishmania donovani

Abstract: The co-infection cases involving dixenous Leishmania spp. (mostly of the L. donovani complex) and presumably monoxenous trypanosomatids in immunocompromised mammalian hosts including humans are well documented. The main opportunistic parasite has been identified as Leptomonas seymouri of the sub-family Leishmaniinae. The molecular mechanisms allowing a parasite of insects to withstand elevated temperature and substantially different conditions of vertebrate tissues are not understood. Here we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
146
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(153 citation statements)
references
References 92 publications
3
146
2
2
Order By: Relevance
“…Genome sequencing and transcriptome profiling identified several adaptations in L . seymouri that allow it to persist in the vertebrate host environment [100]. Furthermore, L .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome sequencing and transcriptome profiling identified several adaptations in L . seymouri that allow it to persist in the vertebrate host environment [100]. Furthermore, L .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, L . seymouri survived for several days in two species of phlebotamine sand fly [100]. Given their close relationship with Leishmania , Leptomonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the most potent enzymes on the Earth with Kcat reaching 10 7 molecules of H 2 0 2 per second. Its presence in all monoxenous relatives of Leishmania (species of Leptomonas Kent, 1880, Crithidia Léger, 1902 and Lotmaria Evans et Schwarz, 2014 of the subfamily Leishmaniinae -see Jirků et al 2012) requires further investigation (Kraeva et al 2015, Flegontov et al 2016. The entire open reading frame of the catalase gene, PCR-amplified from DNA of the H10 isolate of Leptomonas pyrrhocoris Zotta, 1912(Votýpka et al 2012, was integrated into the β-tubulin locus and expressed in a T7 polymerase-dependent, Tet-inducible way.…”
mentioning
confidence: 99%
“…To verify that the decrease of gene expression in metacyclics and amastigotes is not sequence-specific, we replaced the T7 polymerase open reading frame by that of mCherry as described previously (Kraeva et al 2015). The construct was integrated into the same 18S rRNA locus (Kushnir et al 2005) and expression of the mCherry protein was confirmed by fluorescence microscopy (data not shown).…”
mentioning
confidence: 99%